1983
DOI: 10.1128/aem.45.3.898-904.1983
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Degradation by Streptomyces viridosporus : Isolation and Characterization of a New Polymeric Lignin Degradation Intermediate

Abstract: A new, quantitatively significant intermediate formed during lignin degradation by Streptomyces viridosporus T7A was isolated and characterized. In Streptomyces-inoculated cultures, the intermediate, an acid-precipitable, polyphenolic, polymeric lignin (APPL), accumulated in the growth medium. The APPL was a water-soluble polymer probably consisting of a heterogeneous mixture of molecular weight components of .20,000. APPLs were precipitable from culture filtrates after they had been acidified to pH <3 to 5. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(103 citation statements)
references
References 11 publications
6
94
0
Order By: Relevance
“…Decrease in NDF, iNDF and ADF contents in WS by bacterial treatments was similar to the study by Crawford (1978) who reported that the selected strains of Streptomyces degraded 25-40% of cellulose content of lignocellulose after 6 weeks of incubation. Additionally, in the work of Crawford et al (1983), carbohydrate content of corn stem decreased 44Á4% after 8 weeks of incubation with Streptomyces viridosporus. Kerr and Kerr (1987) also degraded 6Á5% of grass polysaccharides after 10 days of incubation with Arthrobacter.…”
Section: Discussionmentioning
confidence: 91%
“…Decrease in NDF, iNDF and ADF contents in WS by bacterial treatments was similar to the study by Crawford (1978) who reported that the selected strains of Streptomyces degraded 25-40% of cellulose content of lignocellulose after 6 weeks of incubation. Additionally, in the work of Crawford et al (1983), carbohydrate content of corn stem decreased 44Á4% after 8 weeks of incubation with Streptomyces viridosporus. Kerr and Kerr (1987) also degraded 6Á5% of grass polysaccharides after 10 days of incubation with Arthrobacter.…”
Section: Discussionmentioning
confidence: 91%
“…Subsequently, attention has focussed on analysis of the products of actinomycete attack in an effort to gain insight into the mechanism of degradation. Some low molecular weight products such as syringic and ferulic acids have been detected [113] but the major product is a high molecular weight complex of lignin, carbohydrate and protein [49,114,115]. Grass lignocelluloses are much more susceptible to actinomycete attack than those of wood [113,114], as indicated by the yields of this water-soluble, acid-precipitable material (APPL) from culture filtrates.…”
Section: Lignin Degradation By Actinomy-cetesmentioning
confidence: 99%
“…Some low molecular weight products such as syringic and ferulic acids have been detected [113] but the major product is a high molecular weight complex of lignin, carbohydrate and protein [49,114,115]. Grass lignocelluloses are much more susceptible to actinomycete attack than those of wood [113,114], as indicated by the yields of this water-soluble, acid-precipitable material (APPL) from culture filtrates. Using ~4C-labelled wheat lignocellulose, McCarthy and Broda [17] found that solubilisation of radiolabelled material (30-40%) occurred during primary growth with no evidence of further significant degradation or mineralisation to CO 2 by fresh cultures of Thin.…”
Section: Lignin Degradation By Actinomy-cetesmentioning
confidence: 99%
“…Lignin degradation products in DOM are almost entirely polymeric, although they are smaller and more polar than lignin itself, because of oxidative degradation (Zech et al, 1992). Crawford et al (1983) showed experimentally that oligomeric structures and water-soluble polymeric materials are formed during fungal decay of lignin. Lignin-type polymeric structures have been found in DOM samples from rivers and lakes (Ertel et al, 1984), and from forest soil leachates (Guggenberger & Zech, 1994).…”
Section: Introductionmentioning
confidence: 99%